THEORETICAL STUDY OF THE EFFECT OF WATER MOLECULE ADDITION ON THE CONFORMATION OF SUBSTITUTED DIBENZO-18-CROWN-6 ETHER IN ITS COMPLEXATION WITH Na+ CATION USING SEMI EMPIRICAL METHOD MNDO/d - Harno Dwi Pranowo; Tuti Hartati Siregar; Mudasir Mudasir (Universitas Gadjah Mada, 2003)
The effect of water molecule addition into modeling structure of complex of substituted dibenzo-18-crown-6 ether with metal ion Na+ was studied. The aim of this research is to find information about geometrical conformation of substituted DB18C6 and its selectivity to complex/coordinate metal ion Na+ in the presence of water molecule. In this research semi empirical method was used for calculation. To find the best conformation, trial and error experiments were conducted using semi empirical method available in HyperChem 6.0, finally MNDO/d method was selected. The result of geometry optimization showed that addition of water molecule improve the stability of the conformation of substituted DB18C6 and increase the selectivity of this compound to complex metal ion Na+. The presence of electron-withdrawing substituents decreased the binding energy while that of electron-donating one increase the binding energy (value of DE more negative). Cavity radii of DB18C6 in the presence of water molecule extended from 2.3 Å to 2.6 Å. This figure is almost similar to that of experimental data.